Application of Letter Card Media in Improving Students' Reading Ability - Fitriyanti Aridin; Yulanti S. Mooduto (Journal of Education Review Provision, 2023)
The study's overarching goal was to ascertain whether or not the use of Letter Cards had any effect on the development of beginning readers in Class II at SDN 01 Duhiadaa in the Duhiadaa District of the Pohuwato Regency. This study employed an action research strategy in the classroom, with 16 students from a second-year high school serving as participants. Planning, implementation, observation, and reflection were the four stages of each study cycle. Students' early reading proficiency in Indonesian topics remains inadequate, according to this study. This is evidenced by students' initially poor reading abilities, which reached 25% in the fewer categories at the time of initial observation, then improved to 56.2% in the sufficient category at the end of the first cycle and then increased to 100% in the very good category at the end of the second cycle. Class II pupils at SDN 01 Duhiadaa in the Duhiadaa District of the Pohuwato Regency can benefit from using letter cards as a form of learning media to advance their early reading skills. Meeting III of Cycle II was called to a close since it had achieved the predetermined performance indicators, in this case 80% of the goals set at the beginning of the cycle.